2015
DOI: 10.1002/smll.201500701
|View full text |Cite
|
Sign up to set email alerts
|

Phytotoxicity, Translocation, and Biotransformation of NaYF4Upconversion Nanoparticles in a Soybean Plant

Abstract: The increasing uses of rare-earth-doped upconversion nanoparticles (UCNPs) have obviously caused many concerns about their potential toxicology on live organisms. In addition, the UCNPs can be released into the environment, then transported into edible crop plants, and finally entered into food chain. Here, the soybean is chosen as a model plant to study the subchronic phytotoxicity, translocation, and biotransformation of NaYF4 UCNPs. The incubation with UCNPs at a relative low concentration of 10 μg mL(-1) l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(29 citation statements)
references
References 49 publications
2
27
0
Order By: Relevance
“…Yin and coworkers chose soybean as a model plant, and investigated the subchronic phytotoxicity, translocation and biotransformation of UCNPs. 140 They found that relative low concentration of UCNPs (10 µg/mL) led to growth promotion for roots and stems, while high concentration of UCNPs (exceed 10 µg/mL) had inhibition effect on the growth of plant during the subchronic incubation time for 22 d.…”
Section: Toxicity Of Ucnpsmentioning
confidence: 98%
“…Yin and coworkers chose soybean as a model plant, and investigated the subchronic phytotoxicity, translocation and biotransformation of UCNPs. 140 They found that relative low concentration of UCNPs (10 µg/mL) led to growth promotion for roots and stems, while high concentration of UCNPs (exceed 10 µg/mL) had inhibition effect on the growth of plant during the subchronic incubation time for 22 d.…”
Section: Toxicity Of Ucnpsmentioning
confidence: 98%
“…However, none of the aforementioned works considered the biotransformation of UCNPs in plants, which could be one of the critical factors affecting plant toxicity. To solve this problem, Yin et al [78] . investigated the toxicity, translocation, and biotransformation of the PEI‐modified NaYF 4 : Yb, Er UCNPs in plants, and using soybean as a model plant.…”
Section: Interaction Between Ucnps and Plantsmentioning
confidence: 99%
“…However, some authors have shown no negative consequences or even biostimulating effect of NPs on plants including oat ( Avena sativa L.), corn ( Zea mays L.), tomato ( Lycopersicon esculentum L.), cress ( Lepidium sativum ), white mustard ( Sinapis alba ) sorghum ( Sorghum saccharatum ), lettuce ( Lactuca sativa L.) and wheat ( Triticum aestivum L.) (2428). The positive effect occurred mainly at low concentrations and was reversed at higher doses of NPs (16,17). The improvement of growth may be caused by more effective uptake of water or nutrients in plants exposed to NPs (17,26,29), as well as interference with the toxic metals taken up from the medium (30,31).…”
Section: Introductionmentioning
confidence: 96%